Brazil new world in the tropics - World Film Productions; TVOntario (Toronto, Ont. : TV Ontario ; Shawnee Mission, Kansas : RMI Productions [distributor], 1981)
Provides an introduction to the study of Brazil from ancient to modern times. Takes the viewer from the first Portuguese exploration of the Brazilian coast in 1490 to the Brazil of today, discussing the various political, religious, social, and economic changes the country has endured.
VHS format.
Keywords: Brazil -- History; Brazil -- Civilization